Effects of deformation of cylindrical compound parabolic concentrator (CPC) on concentration characteristics. (December 2018) - Xu, Rongji; Ma, Yusen; Yan, Meiyu; Zhang, Chao; Xu, Shuhui; Wang, Ruixiang
Highlights: An in-house code was developed to simulate the propagation process of the solar radiation rays. The effect of CPC deformation on the concentrating characteristics was analyzed. Heat flux has two peaks on the external surface of the heat receiver. Certain translation and internal rotation of CPC was allowed. The down offset and right and left offset of the heat receiver should be avoided. Abstract: Compound parabolic concentrators (CPC) have immense potential for middle-and-low temperature heat collection of solar energy. In this study, the propagation process of solar radiation rays in a CPC–tubular solar collector was simulated using an in-house MATLAB code by the Monte Carlo ray tracing (MCRT) method. The effects of ray incidence angle, CPC concentration ratio, and truncation residual ratio on the heat flux distribution on the tubular heat receiver were analyzed. Moreover, the effects of CPC deformations on concentration characteristics were analyzed, involving the rotation and translation of the reflective surface, the truncation of the involute starting point, and the position offset of the heat receiver. The heat flux distribution exhibited two evident peaks on the heat receiver external surface due to the concentration effect of the CPC. A small internal rotation, a small internal or external translation of the reflective surface, and the truncation of the involute starting point had mere effect on the heat flux distribution on the heat receiver. Therefore, the reflective surface can be allowed to have certain translation and internal rotation when machining a CPC. The downward, rightward, and leftward offsets of heat receivers should be avoided in the assembly of heat receivers and CPCs.